Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

A rapid and robust translational model for testicular aging research - N. Schmid; Y. Stepanov; M. Offner; L. Scholz; C. Herrmann; S. Petkov; R. Behr; J. B. Stöckl; T. Fröhlich; A. Mayerhofer (Histochemistry and Cell Biology, 2026)
In humans, testicular peritubular cells (TPCs) form a small compartment surrounding the seminiferous tubules and, as shown previously, undergo age-related changes. How they may contribute to the age-associated decline of testicular functions is not well known. Likewise, the mechanisms of testicular aging in humans are not well examined. This is in part due to the lack of appropriate cellular models. We aimed to establish an aging model of TPCs, which is based on immortalized nonhuman primate (NHP) peritubular cells (iMKTPCs) from Callithrix jacchus . As shown previously by a comprehensive proteomic approach, they strongly resemble human TPCs but lack the human cell-intrinsic heterogeneity. Cellular senescence was robustly induced within 10 days upon exposure to 25 µg/mL bleomycin for 24 h. This resulted in increased β-galactosidase activity, enlarged cells, and elevated transcript levels of senescence-associated secretory phenotype (SASP) molecules ( IL1b , TNFa , CCL2 ). The ability to contract upon a stimulus was reduced, as shown in live cell imaging studies. Reduced proliferation among others was indicated by a decreased abundance of proliferating cell nuclear antigen (PCNA), evident in a proteomic analysis, which also revealed massive changes (341 significantly increased and 372 decreased proteins). Bioinformatics analysis indicated a marked reduction in several cell-motility–associated proteins, whereas proteins linked to extracellular exosomes, the cytoskeleton, and lysosomal pathways were increased in abundance. To conclude, bleomycin treatment causes a rapid and robust induction of cellular senescence in a translational testicular cell model of peritubular cells. This model will enable future studies aiming to explore mechanisms and consequences of testicular aging.

Factors affecting 87Sr/86Sr preservation in conodont apatite: An example from the Ordovician of Baltoscandia - Christopher T. Conwell; Matthew R. Saltzman; Anders Lindskog; Mats E. Eriksson; Elizabeth M. Griffith; Stephen A. Leslie; Cole T. Edwards; Olle Hints; Achim D. Herrmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effect of gillnet mesh size on catch efficiency and bycatch in the Greenlandic lumpfish (Cyclopterus lumpus) fishery - Malthe Kjølhede Ahlmann Olesen; Bent Herrmann; Rikke Petri Frandsen; Flemming R. Merkel; Cas Van Der Kaaden; Søren Post (Estuarine, Coastal and Shelf Science, 2025)

Ecosystem Metabolic Rates Estimated from Diel Oxygen Measurements in Two Subtropical Estuaries - J. M. Arriola; R. G. Najjar; H. Briceño; C. Hu; M. Herrmann; M. W. Beck (Estuaries and Coasts, 2025)
Subtropical estuaries worldwide are facing increasing pressure from human population growth, development, and climate change. Carbon is a useful currency for understanding how estuaries respond to these pressures and yet relatively little is known about carbon cycling in subtropical estuaries. Here we compute gross primary production (GPP), ecosystem respiration (ER), and net ecosystem production (NEP) from the diurnal cycle in dissolved oxygen measured during 38 week-long individual deployments over three years in two estuaries in the southeastern United States, Biscayne Bay and Tampa Bay. On average for both estuaries, GPP and ER nearly balance, with NEP about an order of magnitude smaller. Even though production in Tampa Bay and Biscayne Bay is dominated by different primary producers and limiting nutrients, mean GPP was the same, about 190 mmol O 2 m –2 d –1 (570 g C m –2 y –1 ). Our GPP estimates for Biscayne Bay are more than an order of magnitude greater than the only other productivity estimates available for this system, which are planktonic net primary productivity measurements from the late 1970s. GPP was strongly correlated with water temperature in Biscayne Bay ( r = 0.60) but had the strongest correlation with salinity in Tampa Bay ( r = 0.39). These findings highlight the importance of more frequent production measurements in these complex estuaries, especially in the face of a changing climate.

Temporal Changes to Migratory Fuel Load in Migratory Birds Across Europe - Jennifer Anne Border; Robert A. Robinson; James W. Pearce‐Higgins; Chris M. Hewson; Christine Howard; Philip A. Stephens; Stephen G. Willis; Jan A. C. von Rönn; Pierre‐Yves Henry; Romain Lorrilliere; Lorenzo Serra; Simona Imperio; et al. (Global Change Biology, 2025)
Climate change is a major threat to biodiversity, and migratory animals are particularly vulnerable, due partly to their reliance upon good resource availability across a network of sites at specific times. Migrants perform vital ecosystem functions, transferring significant resources across large spatial scales, but the impacts of climate change on the ability of individuals to complete these journeys are poorly studied. Collecting the large‐scale and long‐term data on the condition of individuals during migration to address this is challenging, but in migratory birds, we have a model system for which a large network of ringers (banders) collect individual data on body size and mass, enabling variation in body condition to be tracked. We used long‐term ringing data on 33 Afro–Palearctic migratory bird species at 286 sites across Europe to demonstrate a large‐scale decrease in migratory fuel loads during autumn over the last 40 years, but not in spring. Declines were strongest across southern Europe and linked to rising temperatures. The timing of autumn fuelling has also shifted, occurring earlier at northern sites and later at southern sites. These relationships varied depending on diet and breeding cycle length. Obligate insectivores were more constrained by temperature in the timing and magnitude of fuelling than frugivores. Species with short breeding cycles departed later at southern sites in warmer years, likely reflecting an extended breeding season. Altogether, these latitudinally varying findings suggest a trade‐off between maximising productivity or maximising adult survival as climate drives changing constraints on breeding season length and resource availability. Similar climate‐induced trade‐offs may be happening in other migratory taxa with the potential to influence population trends.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

Evaluation of behavioral and neurochemical changes induced by carbofuran in zebrafish (Danio rerio) - Giovana R. Oliveira; Matheus Gallas-Lopes; Rafael Chitolina; Leonardo M. Bastos; Stefani M. Portela; Thailana Stahlhofer-Buss; Darlan Gusso; Rosane Gomez; Angela T.S. Wyse; Ana P. Herrmann; Angelo Piato (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Population balance modeling-assisted prediction of oxygen mass transfer coefficients with optical measurements - R. Herrmann-Heber; M. Oleshova; S.F. Reinecke; M. Meier; S. Taş; U. Hampel; A. Lerch (Journal of Water Process Engineering, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Isolating the drivers of the species‐area relationship in experimental habitat islands - Granger W. Hanks; Natalie A. Clay; Maggie Herrmann; Clifton Nunnally; S. River D. Bryant; Craig R. McClain (Journal of Biogeography, 2024)
Aim Considered one of ecology's laws, the species‐area relationship (SAR) is among the most intensively studied ecological phenomena, yet the mechanisms through which the SAR arises and under what circumstances remain poorly understood. Here, we experimentally test the effects of area alone in the absence of commonly invoked mechanistic drivers of the SAR in both sub‐tidal bay and inter‐tidal marsh habitats. Location Louisiana, U.S.A. Taxon Invertebrate macrofauna. Methods To determine if surface area alone may generate the SAR, we conducted a small‐scale, ephemeral habitat island experiment in a subtidal soft‐bottom bay and in an intertidal soft‐bottom coastal salt marsh. Cellulose sponge habitat islands of varying surface areas, but with constant energy content and habitat diversity, were deployed in each location to isolate the effects of surface area on the SAR in the absence of species‐energy relationships and habitat diversity. Results Area alone, likely through passive sampling, generated significant SARs in both habitats, with the salt marsh producing the strongest relationship, likely due to differential physical structuring between habitats. Communities of low surface area sponges were generally nested within those of high surface area sponges, and dispersal limitation may have increased the importance of nestedness relative to species replacements in structuring communities between habitats. Main Conclusions That area alone, in the absence of covariates such as energy availability and habitat diversity may, significantly impact the species richness of experimental and ephemeral marine benthic habitat island communities. Our methodology may provide a new avenue for SAR research, allowing for the isolation and simultaneous testing of potential drivers through the physical manipulation of ephemeral habitats.

Seasonal variations of microplastic pollution in the German River Weser - Sonya R. Moses; Martin G.J. Löder; Frank Herrmann; Christian Laforsch (Science of The Total Environment, 2023)

Seasonal and regional variability of model-based zooplankton biomass in the Salish Sea and evaluation against observations - Karyn D. Suchy; Elise Olson; Susan E. Allen; Moira Galbraith; BethElLee Herrmann; Julie E. Keister; R. Ian Perry; Akash R. Sastri; Kelly Young (Progress in Oceanography, 2023)

Do ticks exhibit repeatable individual behaviors? - Hugh Lefcort; Matthew L. Hovancsek; Lindsey A. Bell; Erin K. Ellinwood; Elizabeth M. Freisinger; Katelin G. Herrmann; Jalisa R. Lau (Experimental and Applied Acarology, 2023)

An estate at Zincirli? Land use and resource exploitation at the Middle Bronze Age monumental building Complex DD in Zincirli, Gaziantep Province of Turkey - Katleen Deckers; Doga Karakaya; Laurel Poolman; Birgül Öğüt; Jason Herrmann; Kathryn R. Morgan; Virginia Herrmann (Archaeological and Anthropological Sciences, 2023)
Near Eastern monumental buildings once hosted institutions with a variety of economic and environmental footprints. In this article examining a Middle Bronze Age II (seventeenth century BC) building complex at Zincirli, Turkey, we integrate bioarchaeological remains with ceramic and artifactual evidence to evaluate whether this building was a specialized node in a broader network and centralized economy. Combining seed/fruit/chaff analysis with charcoal, phytolith, diatom, and spherulite investigations and zooarchaeology allows for a more holistic identification of the building’s environmental and economic catchments. The pronounced presence of conifer, probably related to the building’s architecture, suggests an elite function of the complex. A broad range of activities took place within the complex, such as the preparation, storage, and consumption of different food and drink products, alongside craft activities. There is evidence for centralized storage of diverse crops and production of wine and textiles. The building seems to have functioned as a kind of estate, possessing access to large areas of land. The bioarchaeological remains evidence the exploitation of the varied environments surrounding the site, where economically valuable resources were locally available and exploited, such as cedar, pine, grapes, and large hunting game. Complex DD provides evidence of wetland exploitation, agropastoral production, wood procurement, and hunting in the semi-steppe batha environments of the Islahiye plain and the woodland forests of the Amanus.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Early environmental enrichment and impoverishment differentially affect addiction-related behavioral traits, cocaine-taking, and dopamine D2/3 receptor signaling in a rat model of vulnerability to drug abuse - Lidia Bellés; Andrea Dimiziani; François R. Herrmann; Nathalie Ginovart (Psychopharmacology, 2021)
Rationale Risk factors for drug addiction include genetics, environment, and behavioral traits such as impulsivity and novelty preference (NP), which have been related to deficits in striatal dopamine (DA) D 2/3 -receptors (D 2/3 R) and heightened amphetamine (AMPH)-induced DA release. However, the influence of the early rearing environment on these behavioral and neurochemical variables is not clear. Objectives We investigated the influence of early rearing environment on striatal D 2/3 R availabilities and AMPH-induced DA release in relation to impulsivity, NP, and propensity to drug self-administration (SA) in “addiction-prone” Roman high- (RHA) and “addiction-resistant” Roman low-avoidance (RLA) rats. Methods Animals were reared post-weaning in either environmental enrichment (EE) or impoverishment (EI) and were assessed at adulthood for impulsivity, NP, and propensity to cocaine SA. EE and EI rats were also scanned using single-photon emission computed tomography to concurrently measure in vivo striatal D 2/3 R availability and AMPH-induced DA release. Results EE vs. EI was associated with heightened impulsivity and a lack of NP in both rat lines. Higher dorsal striatal D 2/3 R densities were found in RHA EE and higher AMPH-induced DA release in RLA EE. Both impulsivity and NP were negatively correlated to dorsal striatal D 2/3 R availabilities and positively correlated with AMPH-induced DA release in EI but not in EE. EE vs. EI was related to a faster rate of cocaine intake and elevated active timeout responses in RHAs. Conclusion Our results suggest non-monotonic, environment-dependent, relationships between impulsivity, NP, and D 2/3 R-mediated signaling, and suggest that EI vs. EE may decrease the reinforcing effects of psychostimulants in predisposed individuals.

Hippocampal and Prefrontal Cortical Brain Tissue Levels of Irisin and GDF15 Receptor Subunits in Children - Travis C. Jackson; Kiersten Gorse; Jeremy R. Herrmann; Patrick M. Kochanek (Molecular Neurobiology, 2021)
Cold-stress hormones (CSHs) stimulate thermogenesis and have direct neuroprotective effects on the brain. The obligatory receptor components of two new CSHs (irisin and growth differentiation factor-15 [GDF15]) were recently discovered. Irisin binds integrin-αV/β5 heterodimers while GDF-15 binds to the orphan receptor glial cell-derived neurotrophic factor (GDNF) family receptor α-like (GFRAL). In addition, integrin-αV/β5 was just identified as the key receptor mediating Zika virus infection in the CNS. We measured integrin-αV, integrin-β5, and GFRAL protein levels across 78 high-quality human male/female brain tissues in infants, toddlers, preschoolers, adolescent, and adults—providing the most robust analysis to date on their levels in the human cortex and hippocampus. We report that integrin-αV was detected at all ages in the prefrontal cortex with levels greatest in adults. Integrin-αV was also detected in the hippocampus in all age groups. In contrast, integrin-β5 was detected in cortex and hippocampus largely restricted to infants. Co-expression of integrin-αV/β5 in the human infant hippocampus and cortex suggests the possibility that irisin has a more robust effect on the developing vs. the adult brain and may have implications for Zika virus infection in infants and young children.

Long-Term Impacts of Invasive Insects and Pathogens on Composition, Biomass, and Diversity of Forests in Virginia’s Blue Ridge Mountains - Kristina J. Anderson-Teixeira; Valentine Herrmann; Wendy B. Cass; Alan B. Williams; Stephen J. Paull; Erika B. Gonzalez-Akre; Ryan Helcoski; Alan J. Tepley; Norman A. Bourg; Christopher T. Cosma; Abigail E. Ferson; Caroline Kittle; et al. (Ecosystems, 2021)

Toxicokinetics and toxicodynamics of the fentanyl homologs cyclopropanoyl-1-benzyl-4´-fluoro-4-anilinopiperidine and furanoyl-1-benzyl-4-anilinopiperidine - Tanja M. Gampfer; Lea Wagmann; Yu Mi Park; Annelies Cannaert; Jennifer Herrmann; Svenja Fischmann; Folker Westphal; Rolf Müller; Christophe P. Stove; Markus R. Meyer (Archives of Toxicology, 2020)
The two fentanyl homologs cyclopropanoyl-1-benzyl-4´-fluoro-4-anilinopiperidine (4F-Cy-BAP) and furanoyl-1-benzyl-4-anilinopiperidine (Fu-BAP) have recently been seized as new psychoactive substances (NPS) on the drugs of abuse market. As their toxicokinetic and toxicodynamic characteristics are completely unknown, this study focused on elucidating their in vitro metabolic stability in pooled human liver S9 fraction (pHLS9), their qualitative in vitro (pHLS9), and in vivo (zebrafish larvae) metabolism, and their in vitro isozyme mapping using recombinant expressed isoenzymes. Their maximum-tolerated concentration (MTC) in zebrafish larvae was studied from 0.01 to 100 µM. Their µ-opioid receptor (MOR) activity was analyzed in engineered human embryonic kidney (HEK) 293 T cells. In total, seven phase I and one phase II metabolites of 4F-Cy-BAP and 15 phase I and four phase II metabolites of Fu-BAP were tentatively identified by means of liquid chromatography high-resolution tandem mass spectrometry, with the majority detected in zebrafish larvae. N -Dealkylation, N -deacylation, hydroxylation, and N -oxidation were the most abundant metabolic reactions and the corresponding metabolites are expected to be promising analytical targets for toxicological analysis. Isozyme mapping revealed the main involvement of CYP3A4 in the phase I metabolism of 4F-Cy-BAP and in terms of Fu-BAP additionally CYP2D6. Therefore, drug-drug interactions by CYP3A4 inhibition may cause elevated drug levels and unwanted adverse effects. MTC experiments revealed malformations and changes in the behavior of larvae after exposure to 100 µM Fu-BAP. Both substances were only able to produce a weak activation of MOR and although toxic effects based on MOR activation seem unlikely, activity at other receptors cannot be excluded.

Differential Bioaccumulation of Mercury and Selenium in Stomach Contents and Tissues of Three Colorado, USA, Cutthroat Trout Populations - Scott J. Herrmann; Del Wayne R. Nimmo; James S. Carsella; Igor V. Melnykov; Christopher M. Kennedy; Kevin B. Rogers; Lynn M. Herrmann-Hoesing (Bulletin of Environmental Contamination and Toxicology, 2020)

The nature and origin of pigments in black opal from Lightning Ridge, New South Wales, Australia - J. R. Herrmann; R. Maas; P. F. Rey; S. P. Best (Australian Journal of Earth Sciences, 2019)

Connectivity increases trophic subsidies in fragmented landscapes - Christine L. Hawn; John D. Herrmann; Sean R. Griffin; Nick M. Haddad (Ecology Letters, 2018)
Landscape corridors mitigate the negative effects of habitat fragmentation by increasing dispersal. Corridors also increase biodiversity in connected habitat fragments, suggestive of metacommunity dynamics. What is unknown in this case is the mechanisms through which metacommunity dynamics act. Working in a large‐scale fragmentation experiment, we tested the effect of corridors on the movement of prey species and subsequent effects on predator nutrition (which we call trophic subsidies). We enriched plants of central patches with 15 N, then measured δ 15 N in green lynx spiders, the most abundant insect predator, in patches that were either connected to or isolated from the enriched patch. We found that corridors increased prey movement, as they increased spider δ 15 N by 40% in connected patches. Corridors also improved spider body condition, increasing nitrogen relative to carbon. We suggest a novel mechanism, trophic subsidies, through which corridors may increase the stability or size of populations in connected landscapes.

Creep of Posidonia Shale at Elevated Pressure and Temperature - E. Rybacki; J. Herrmann; R. Wirth; G. Dresen (Rock Mechanics and Rock Engineering, 2017)

Field studies measuring the aerosolization of endotoxin during the land application of Class B biosolids - R. F. Herrmann; R. J. Grosser; D. Farrar; R. B. Brobst (Aerobiologia, 2017)

Peripheral Alterations in Cytokine and Chemokine Levels After Antidepressant Drug Treatment for Major Depressive Disorder: Systematic Review and Meta-Analysis - Cristiano A. Köhler; Thiago H. Freitas; Brendon Stubbs; Michael Maes; Marco Solmi; Nicola Veronese; Nayanna Q. de Andrade; Gerwyn Morris; Brisa S. Fernandes; André R. Brunoni; Nathan Herrmann; Charles L. Raison; et al. (Molecular Neurobiology, 2017)

Evaluation of nutria (Myocastor coypus) detection methods in Maryland, USA - Margaret A. Pepper; Valentine Herrmann; James E. Hines; James D. Nichols; Stephen R. Kendrot (Biological Invasions, 2017)

The role of digital data entry in participatory environmental monitoring - Jeremy R. Brammer; Nicolas D. Brunet; A. Cole Burton; Alain Cuerrier; Finn Danielsen; Kanwaljeet Dewan; Thora Martina Herrmann; Micha V. Jackson; Rod Kennett; Guillaume Larocque; Monica Mulrennan; Arun Kumar Pratihast; et al. (Conservation Biology, 2016)
Many argue that monitoring conducted exclusively by scientists is insufficient to address ongoing environmental challenges. One solution entails the use of mobile digital devices in participatory monitoring (PM) programs. But how digital data entry affects programs with varying levels of stakeholder participation, from nonscientists collecting field data to nonscientists administering every step of a monitoring program, remains unclear. We reviewed the successes, in terms of management interventions and sustainability, of 107 monitoring programs described in the literature (hereafter programs) and compared these with case studies from our PM experiences in Australia, Canada, Ethiopia, Ghana, Greenland, and Vietnam (hereafter cases). Our literature review showed that participatory programs were less likely to use digital devices, and 2 of our 3 more participatory cases were also slow to adopt digital data entry. Programs that were participatory and used digital devices were more likely to report management actions, which was consistent with cases in Ethiopia, Greenland, and Australia. Programs engaging volunteers were more frequently reported as ongoing, but those involving digital data entry were less often sustained when data collectors were volunteers. For the Vietnamese and Canadian cases, sustainability was undermined by a mismatch in stakeholder objectives. In the Ghanaian case, complex field protocols diminished monitoring sustainability. Innovative technologies attract interest, but the foundation of effective participatory adaptive monitoring depends more on collaboratively defined questions, objectives, conceptual models, and monitoring approaches. When this foundation is built through effective partnerships, digital data entry can enable the collection of more data of higher quality. Without this foundation, or when implemented ineffectively or unnecessarily, digital data entry can be an additional expense that distracts from core monitoring objectives and undermines project sustainability. The appropriate role of digital data entry in PM likely depends more on the context in which it is used and less on the technology itself.

Prevention of unpredictable chronic stress-related phenomena in zebrafish exposed to bromazepam, fluoxetine and nortriptyline - Matheus Marcon; Ana P. Herrmann; Ricieri Mocelin; Cassiano L. Rambo; Gessi Koakoski; Murilo S. Abreu; Greicy M. M. Conterato; Luiza W. Kist; Maurício R. Bogo; Leila Zanatta; Leonardo J. G. Barcellos; Angelo L. Piato (Psychopharmacology, 2016)

HC-Induced Deactivation in CO Conversion at Diesel Oxidation Catalysts - M. Herrmann; S. Malmberg; A. Drochner; H. Vogel; R. Hayes; M. Votsmeier (Emission Control Science and Technology, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Differential Accumulation of Mercury and Selenium in Brown Trout Tissues of a High-Gradient Urbanized Stream in Colorado, USA - S. J. Herrmann; D. R. Nimmo; J. S. Carsella; L. M. Herrmann-Hoesing; J. A. Turner; J. M. Gregorich; B. D. Vanden Heuvel; R. B. Nehring; H. P. Foutz (Archives of Environmental Contamination and Toxicology, 2016)

Photocatalytic abatement results from a model street canyon - M. Gallus; R. Ciuraru; F. Mothes; V. Akylas; F. Barmpas; A. Beeldens; F. Bernard; E. Boonen; A. Boréave; M. Cazaunau; N. Charbonnel; H. Chen; et al. (Environmental Science and Pollution Research, 2015)

miR-375 gene dosage in pancreatic β-cells: implications for regulation of β-cell mass and biomarker development - Mathieu Latreille; Karolin Herrmanns; Neil Renwick; Thomas Tuschl; Maciej T. Malecki; Mark I. McCarthy; Katharine R. Owen; Thomas Rülicke; Markus Stoffel (Journal of Molecular Medicine, 2015)

Modelling multiphase chemistry in deliquescent aerosols and clouds using CAPRAM3.0i - A. Tilgner; P. Bräuer; R. Wolke; H. Herrmann (Journal of Atmospheric Chemistry, 2013)

Reference ranges and cutoff levels of pneumococcal antibody global serum assays (IgG and IgG2) and specific antibodies in healthy children and adults - M. A. Rose; J. Buess; Y. Ventur; S. Zielen; E. Herrmann; J. Schulze; R. Schubert (Medical Microbiology and Immunology, 2013)

Functional responses of juvenile herring and sprat in relation to different prey types - R. Brachvogel; L. Meskendahl; J.-P. Herrmann; A. Temming (Marine Biology, 2013)

Bioaccumulation of Selenium by the Bryophyte Hygrohypnum ochraceum in the Fountain Creek Watershed, Colorado - S. J. Herrmann; J. A. Turner; J. S. Carsella; D. W. Lehmpuhl; D. R. Nimmo (Environmental Management, 2012)

The missing host hypothesis: do chemical cues from predators induce life cycle truncation of trematodes within their fish host? - K. K. Herrmann; R. Poulin (Journal of Fish Biology, 2012)
Using controlled experiments, the ability of the trematode parasite Stegodexamene anguillae , encysted within its intermediate fish host, the common bully Gobiomorphus cotidianus , was tested to indirectly detect the presence of its definitive host by exposing infected G. cotidianus to chemical cues from the definitive host, the short‐finned eel Anguilla australis . The trematode can abbreviate its normal life cycle and achieve precocious maturity in G. cotidianus , or adopt the usual strategy consisting in delaying maturity until it reaches an A. australis . The results suggest that chemical cues from the definitive A. australis host do not affect the frequency of life cycle abbreviation in S. anguillae . Other life‐history traits, such as parasite body size or the egg output of early‐maturing parasites, were also unaffected by chemical cues from A. australis or from an alternative predator of G. cotidianus , the perch Perca fluviatilis , that is not a suitable host for the trematode. Therefore, factors other than A. australis host presence or abundance may be the important selective forces for life cycle abbreviation in this fish parasite.

Resurrecting an extinct species: archival DNA, taxonomy, and conservation of the Vegas Valley leopard frog - Evon R. Hekkala; Raymond A. Saumure; Jef R. Jaeger; Hans-Werner Herrmann; Michael J. Sredl; David F. Bradford; Danielle Drabeck; Michael J. Blum (Conservation Genetics, 2011)

Response of a Coupled Ocean–Atmosphere Model to Greenland Ice Melting - D. Stammer; N. Agarwal; P. Herrmann; A. Köhl; C. R. Mechoso (Surveys in Geophysics, 2011)

Sex differences in cognitive control are associated with midcingulate and callosal morphology - Rene J. Huster; R. Westerhausen; C. S. Herrmann (Brain Structure and Function, 2011)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

Obesity is associated with improved survival in patients with organ-confined clear-cell kidney cancer - Sandra Waalkes; Axel S. Merseburger; Mario W. Kramer; Thomas R. W. Herrmann; Gerd Wegener; Julia Rustemeier; Rainer Hofmann; Mark Schrader; Markus A. Kuczyk; Andres J. Schrader (Cancer Causes & Control, 2010)

Thermodynamic properties of sea air - R. Feistel; D. G. Wright; H.-J. Kretzschmar; E. Hagen; S. Herrmann; R. Span (Ocean Science, 2010)
Very accurate thermodynamic potential functions are available for fluid water, ice, seawater and humid air covering wide ranges of temperature and pressure conditions. They permit the consistent computation of all equilibrium properties as, for example, required for coupled atmosphere-ocean models or the analysis of observational or experimental data. With the exception of humid air, these potential functions are already formulated as international standards released by the International Association for the Properties of Water and Steam (IAPWS), and have been adopted in 2009 for oceanography by IOC/UNESCO. In this paper, we derive a collection of formulas for important quantities expressed in terms of the thermodynamic potentials, valid for typical phase transitions and composite systems of humid air and water/ice/seawater. Particular attention is given to equilibria between seawater and humid air, referred to as "sea air" here. In a related initiative, these formulas will soon be implemented in a source-code library for easy practical use. The library is primarily aimed at oceanographic applications but will be relevant to air-sea interaction and meteorology as well. The formulas provided are valid for any consistent set of suitable thermodynamic potential functions. Here we adopt potential functions from previous publications in which they are constructed from theoretical laws and empirical data; they are briefly summarized in the appendix. The formulas make use of the full accuracy of these thermodynamic potentials, without additional approximations or empirical coefficients. They are expressed in the temperature scale ITS-90 and the 2008 Reference-Composition Salinity Scale.

Ovine progressive pneumonia provirus levels associate with breed and Ovar-DRB1 - Lynn M. Herrmann-Hoesing; Stephen N. White; Michelle R. Mousel; Gregory S. Lewis; Donald P. Knowles (Immunogenetics, 2008)

Complete nucleotide sequence of the Oenothera elata plastid chromosome, representing plastome I of the five distinguishable Euoenothera plastomes - H. Hupfer; M. Swiatek; S. Hornung; R. G. Herrmann; R. M. Maier; W.-L. Chiu; B. Sears (Molecular Genetics and Genomics, 2008)

Genomic analysis of Ovis aries (Ovar) MHC class IIa loci - Lynn M. Herrmann-Hoesing; Stephen N. White; Lowell S. Kappmeyer; David R. Herndon; Donald P. Knowles (Immunogenetics, 2008)

Hypothesis: human serum-borne albumin bound lipids promote cellular survival after apoptosis induction by a variety of stimuli - Martin Schiller; Sandra Franz; Petra Heyder; Reinhard E. Voll; Udo S. Gaipl; Hanns-Martin Lorenz; Joachim R. Kalden; Martin Herrmann (Apoptosis, 2008)

Ground-Motion Scaling in the Western Alps - Paola Morasca; Luca Malagnini; Aybige Akinci; Daniele Spallarossa; R. B. Herrmann (Journal of Seismology, 2006)

Root-to-shoot signalling: apoplastic alkalinization, a general stress response and defence factor in barley (Hordeum vulgare) - H. H. Felle; A. Herrmann; R. Hückelhoven; K.-H. Kogel (Protoplasma, 2005)

Induction of apoptosis by spermine-metabolites in primary human blood cells and various tumor cell lines - M. Schiller; N. Blank; P. Heyder; M. Herrmann; U. S. Gaipl; J. R. Kalden; H. M. Lorenz (Apoptosis, 2005)

Frequency of Norovirus in stool samples from patients with gastrointestinal symptoms in Switzerland - R. Fretz; L. Herrmann; A. Christen; P. Svoboda; O. Dubuis; E. H. Viollier; M. Tanner; A. Baumgartner (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Comparative analysis of adenoviral transgene delivery via tail or portal vein into rat liver - J. Herrmann; B. Abriss; E. van de Leur; S. Weiskirchen; A. M. Gressner; R. Weiskirchen (Archives of Virology, 2004)

Swiss Mattenklee landraces, a distinct and diverse genetic resource of red clover (Trifolium pratense L.) - R. Kölliker; D. Herrmann; B. Boller; F. Widmer (Theoretical and Applied Genetics, 2003)

Effects of selective inactivation of individual genes for low-molecular-mass subunits on the assembly of photosystem II, as revealed by chloroplast transformation: the psbEFLJ operon in Nicotiana tabacum - M. Swiatek; R. E. Regel; J. Meurer; G. Wanner; H. B. Pakrasi; I. Ohad; R. G. Herrmann (Molecular Genetics and Genomics, 2003)

Molecular analysis of aerobic phenylacetate degradation in Azoarcus evansii - R. Rost; S. Haas; E. Hammer; H. Herrmann; G. Burchhardt (Molecular Genetics and Genomics, 2002)

Treatment of Severe Candida Infections in High-Risk Patients in Germany: Consensus Formed by a Panel of Interdisciplinary Investigators - Büchner T.; Fegeler W.; Bernhardt H.; Brockmeyer N.; Duswald K.-H.; Herrmann M.; Heuser D.; Jehn U.; Just-Nübling G.; Karthaus M.; Maschmeyer G.; Müller F.-M.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

C-to-U conversion in the intercistronic ndhI/ndhG RNA of plastids from monocot plants: conventional editing in an unconventional small reading frame? - A. Drescher; H. Hupfer; C. Nickel; F. Albertazzi; U. Hohmann; R. Herrmann; R. Maier (Molecular Genetics and Genomics, 2002)

Scenarios for Modeling Multiphase Tropospheric Chemistry - D. Poppe; B. Aumont; B. Ervens; H. Geiger; H. Herrmann; E.-P. Röth; W. Seidl; W. R. Stockwell; B. Vogel; S. Wagner; D. Weise (Journal of Atmospheric Chemistry, 2001)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Role of apoptosis in autoimmunity - H-M. Lorenz; M. Herrmann; T. Winkler; U. Gaipl; J. R. Kalden (Apoptosis, 2000)

Human astrovirus isolation and propagation in multiple cell lines - J. P. Brinker; N. R. Blacklow; J. E. Herrmann (Archives of Virology, 2000)

CAPRAM2.3: A Chemical Aqueous Phase Radical Mechanism for Tropospheric Chemistry - H. Herrmann; B. Ervens; H.-W. Jacobi; R. Wolke; P. Nowacki; R. Zellner (Journal of Atmospheric Chemistry, 2000)

A polymorphism of the rat T-cell receptor β-chain variable gene 13 ( BV13S1 ) correlates with the frequency of BV13S1-positive CD4 cells - M. Stienekemeier; K. Hofmann; R. Gold; T. Herrmann (Immunogenetics, 2000)

Analysis of single-nucleotide polymorphisms in the interleukin-4 receptor gene for association with inflammatory bowel disease - M. Olavesen; J. Hampe; M. M. Mirza; R. Saiz; C. M. Lewis; S. Bridger; D. Teare; D. F. Easton; T. Herrmann; G. Scott; J. Hirst; J. Sanderson; et al. (Immunogenetics, 2000)

Protein-Surfactant interactions in the defensive skin secretion of the Red Sea trunkfish Ostracion cubicus - E. Kalmanzon; E. Zlotkin; R. Aknin-Herrmann (Marine Biology, 1999)

Physical mapping and molecular-cytogenetic analysis of substitutions and translocations involving chromosome 1D in synthetic hexaploid triticale - U. Hohmann; J. Zoller; R. G. Herrmann; M. E. Kazman (Theoretical and Applied Genetics, 1999)

Diurnal changes in xylem pressure and mesophyll cell turgor pressure of the lianaTetrastigma voinierianum: The role of cell turgor in long-distance water transport - F. Thrmer; J. J. Zhu; N. Gierlinger; H. Schneider; R. Benkert; P. Gener; B. Herrmann; F. -W. Bentrup; U. Zimmerniann (Protoplasma, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Tissue culture of wild-type, interspecific genome/plastome hybrids and plastome mutants of evening primrose ( Oenothera) : controlled morphogenesis and transformation - A. Mehra-Palta; H.-U. Koop; S. Goes; E.-M. Troidl; G. Nagy; S. Tyagi; W. Kofer; R. G. Herrmann (Plant Cell Reports, 1998)

Plant regeneration from leaf protoplasts of evening primrose ( Oenothera hookeri ) - N. Kuchuk; R. G. Herrmann; H.-U. Koop (Plant Cell Reports, 1998)

UV-B Irradiated Cell Lines Execute Programmed Cell Death in Various Forms - M. Hagenhofer; H. Germaier; C. Hohenadl; P. Rohwer; J. R. Kalden; M. Herrmann (Apoptosis, 1998)

Time behavior of topological ordering in self-organizing feature mapping - R. Der; M. Herrmann; T. Villmann (Biological Cybernetics, 1997)

Notification of Retraction: Interleukin 5 expressing allergen-specific T-lymphocytes in patients with house dust mite sensitization: analysis at a clonal level (1995) (J Mol Med 73(2):79-83 - R. Bonifer; C. Neumann; S. Meuer; G. Schulze; F. Herrmann (Journal of Molecular Medicine, 1997)

Approaches to the prevention and control of skin cancer - Scott R. Cummings; Mary K. Tripp; Nancy B. Herrmann (Cancer and Metastasis Reviews, 1997)

Immunological characterization of the Marin County strain of astrovirus - J. E. Herrmann; W. D. Cubitt; R. W. Hudson; Dorothy M. Perron-Henry; L. S. Oshiro; N. R. Blacklow (Archives of Virology, 1990)

Plaque quantitation and virus neutralization assays for human astroviruses - R. W. Hudson; J. E. Herrmann; N. R. Blacklow (Archives of Virology, 1989)

Preparation and characterization of monoclonal antibodies to enteric adenovirus types 40 and 41 - J. E. Herrmann; Dorothy M. Perron-Henry; Darlene Stobbs-Walro; N. R. Blacklow (Archives of Virology, 1987)

Results of chromosome analysis of rabies virus infected human diploid cells (WI-38) - M. Majer; Annelies Herrmann; R. Mauler (Archives of Virology, 1977)

Zur Pyruvat- und ?-Ketoglutaratausscheidung durch Streptomyces rimosus - E.-J. Bormann; R. Herrmann (Archives of Microbiology, 1968)